Positive regulation of innate immune response by miRNA-let-7a-5p - Ueta, Mayumi; Nishigaki, Hiromi; Komai, Seitaro; Mizushima, Katsura; Tamagawa-Mineoka, Risa; Naito, Yuji; Katoh, Norito; Sotozono, Chie; Kinoshita, Shigeru (Frontiers in Genetics, 2023)
Background We previously reported that miR-628-3p negatively regulated innate immunity by suppressing pathogen-associated molecular patterns such as TLR3, RIG-I, and MDA-5, and that that plasma miR-628-3p was up-regulated in atopic dermatitis (AD) with severe allergic conjunctival disease (ACD) with giant papillae, but not in severe AD without severe ACD, nor in our healthy controls. Here to investigate the pathogenesis of AD with and without severe ACD, we performed comprehensive plasma miRNA analysis and studied the function of some miRNAs which was significantly up-regulated in ACD. Methods We subjected plasma from 9 individuals (AD, severe ACD, controls: n = 3 each) to comprehensive miRNA analysis by microarray. To confirm up-regulation, we performed quantitative miRNA polymerase chain reaction (PCR) assays using 80 plasma samples (AD: 23, severe ACD: 17, controls: 40). To study the function of some miRNAs which was significantly up-regulated in ACD, we transfected its mimic respectively to THP-1 cells, a monocyte cell line, and performed comprehensive gene expression analysis of them. The up-regulation of gene expression of interest in transfected THP-1 cells with the hsa-let-7a-5p miRNA mimic was confirmed by quantitative RT-qPCR assay. Results Quantitative miRNA PCR assays showed that hsa-let-7a-5p, hsa-let-7d-3p, hsa-let-7e-5p and hsa-miR-151a-5p were significantly up-regulated in both AD-ACD+ and AD-ACD- as were hsa-miR-130a-3p, hsa-miR-151a-3p, has-miR-27b-3p, and hsa-miR-146a-5p in AD-ACD+ but not in AD-ACD-. The functions of each miRNA were investigated by comprehensive gene expression analysis of THP-1 cells transfected with each miRNA mimic. Quantitative RT-qPCR assays of transfected THP-1 cells with the hsa-let-7a-5p miRNA mimic showed that the 17 genes up-regulated more than 10-fold in the comprehensive gene expression analysis, and TLR3, RIG-I, and MDA5, important innate immune-related genes, were significantly upregulated. TNFSF13B, AIM2, USP41, STAP1, GBP4, CCL8, and IFI27, reportedly down-regulated by the hsa-miR-628-3p mimic, were also significantly up-regulated in the transfected cells. Conclusion Hsa-let-7a-5p, which was significantly up-regulated in AD-ACD+ and AD-ACD-, could positive regulate the important innate immune related genes such as TLR3, RIG-I, and MDA5. It is possible that in the allergic disease such as atopic keratoconjunctivitis and/or dermatitis, innate immune responses might be positive regulated by the hsa-let-7a-5p in the plasma.